Vous êtes sur la page 1sur 6

SIM 1001 Basic Mathematics

2016/2017 Semester 1
Suggested Solutions
1. (a) Let 𝑃(𝑛) be a proposition for 𝑛 ∈ ℕ. Let 𝑘, 𝑙 ∈ ℕ. If the following two
propositions hold:
1. 𝑃(𝑘) is true.
2. 𝑃(𝑘) ∨ 𝑃(𝑘 + 1) … ∨ 𝑃(𝑙) is true implies 𝑃(𝑙 + 1) is true
Then 𝑃(𝑛) is true for all natural numbers 𝑛 ≥ 𝑘.

(i) Let 𝑛 be the amount of postage of stamps, 𝑛 ∈ ℕ. Open statement:


𝑝(𝑛): ∀𝑛 ≥ 30, ∃𝑠, 𝑡 ∈ ℕ ∪ {0} such that 𝑛 = 4𝑠 + 11𝑡.

(ii) Basis step: 𝑝(𝑛) is true for 𝑛 = 30, 31, 32, 33.
𝑝(30): 30 = 4(2) + 11(2), hence 𝑝(30) is true.
𝑝(31): 31 = 4(5) + 11(1), hence 𝑝(31) is true.
𝑝(32): 32 = 4(8) + 11(0), hence 𝑝(32) is true.
𝑝(33): 33 = 4(0) + 11(3), hence 𝑝(33) is true.

(iii) Inductive step: If 𝑝(𝑛) is true then 𝑝(𝑛 + 4) is also true.

Proof: Assume that ∃𝑠, 𝑡 ∈ ℕ ∪ {0} such that 𝑛 = 4𝑠 + 11𝑡. Then


𝑝(𝑛 + 4) = 𝑛 + 4 = 4𝑠 + 4 + 11𝑡 = 4(𝑠 + 1) + 11𝑡
Since 𝑠 ∈ ℕ ∪ {0}, 𝑠 + 1 ∈ ℕ ∪ {0} and thus 𝑝(𝑛 + 4) is true.

(b) 𝑆 is a relation on 𝐴 if 𝑆 is a subset of the Cartesian product 𝐴×𝐴.


Since (3)(3) = 9, 3 /𝑆 3, so 𝑆 is not reflexive.
𝑥𝑦 = 𝑦𝑥 for 𝑥, 𝑦 ∈ ℝ. If 𝑥𝑦 is even, then 𝑦𝑥 is also even.
Since 𝑥 𝑆 𝑦 implies 𝑦 𝑆 𝑥, 𝑆 is symmetric.
3(2) = 6, (2)(5) = 10, (3)(5) = 15.
Since 3 𝑆 2 and 2 𝑆 5 but 3 /𝑆 5, 𝑆 is not transitive.
(c) 𝑝(𝑥) = 𝑥 5 + 5𝑥 4 + 8𝑥 3 + 40𝑥 2 + 16𝑥 + 80
Possible values of 𝑎: ± 1
Possible values of 𝑏: ± 1, ±2, ±4, ±5, ±8, ±10, ±16, ±20, ±40, ±80
Hence by rational root theorem, possible rational roots are
±1, ±2, ±4, ±5, ±8, ±10, ±16, ±20, ±40, ±80.
𝑝(−5) = 0, hence 𝑥 + 5 is a factor.
𝑝(𝑥) = (𝑥 + 5)(𝑥 4 + 8𝑥 2 + 16) = (𝑥 + 5)(𝑥 2 + 4)2

2. (a) √3 1 𝜋 𝜋
√3 + 𝑖 = 2 ( + 𝑖) = 2 (cos + 𝑖 sin )
2 2 6 6
102
(√3 + 𝑖) = 2102 (cos 17𝜋 + 𝑖 sin 17𝜋) = −2102 − (1)

√3 1 𝜋 𝜋
√3 − 𝑖 = 2 ( − 𝑖) = 2 (cos − + 𝑖 sin − )
2 2 6 6
102
(√3 − 𝑖) = 2102 (cos −17𝜋 + 𝑖 sin −17𝜋) = −2102 − (2)
102 102
(1) + (2): (√3 + 𝑖) + (√3 − 𝑖) = −2. 2102 = −2103

(b)

Applying the law of cosines on the triangle above:


|𝑧 + 𝑤|2 = |𝑧|2 + |𝑤|2 − 2|𝑧||𝑤| cos 𝜃
Since cos 𝜃 ≥ −1 and |𝑧|, |𝑤| ≥ 0:
−2|𝑧||𝑤| cos 𝜃 ≤ 2|𝑧||𝑤|
|𝑧 + 𝑤|2 − |𝑧|2 − |𝑤|2 ≤ 2|𝑧||𝑤|
|𝑧 + 𝑤|2 ≤ |𝑧|2 + |𝑤|2 + 2|𝑧||𝑤|
|𝑧 + 𝑤|2 ≤ (|𝑧| + |𝑤|)2
Since |𝑧 + 𝑤|, |𝑧| + |𝑤| ≥ 0, square rooting both sides give:
|𝑧 + 𝑤| ≤ |𝑧| + |𝑤|
Replacing 𝑤 with 𝑤 − 𝑧 in the above equation yields:
|𝑧 + 𝑤 − 𝑧| ≤ |𝑧| + |𝑤 − 𝑧|
|𝑤| − |𝑧| ≤ |𝑤 − 𝑧|
Since |𝑎| = | − 𝑎| for 𝑎 ∈ ℂ, |𝑤 − 𝑧| = |𝑧 − 𝑤|;
|𝑤| − |𝑧| ≤ |𝑧 − 𝑤|

(c) 1 1
2|cos 2𝑥| = 1 → cos 2𝑥 = , −
(i) 2 2
𝑥 ∈ [0, 2𝜋) → 2𝑥 ∈ [0, 4𝜋)
1 𝜋 5𝜋 7𝜋 11𝜋
cos 2𝑥 =→ 2𝑥 = , , ,
2 3 3 3 3
𝜋 5𝜋 7𝜋 11𝜋
𝑥= , , ,
6 6 6 6
1 2𝜋 4𝜋 8𝜋 10𝜋
cos 2𝑥 = − → 2𝑥 = , , ,
2 3 3 3 3
𝜋 2𝜋 4𝜋 5𝜋
𝑥= , , ,
3 3 3 3

(ii)
𝑧 = cos 𝑥 + 𝑖 sin 𝑥
𝑧 𝑧̅ cos 𝑥 + 𝑖 sin 𝑥 cos 𝑥 − 𝑖 sin 𝑥
+ = +
𝑧̅ 𝑧 cos 𝑥 − 𝑖 sin 𝑥 cos 𝑥 + 𝑖 sin 𝑥
(cos 𝑥 + 𝑖 sin 𝑥)2 (cos 𝑥 − 𝑖 sin 𝑥)2
= +
𝑐𝑜𝑠 2 𝑥 + 𝑠𝑖𝑛2 𝑥 𝑐𝑜𝑠 2 𝑥 + 𝑠𝑖𝑛2 𝑥
= 2𝑐𝑜𝑠 2 𝑥 − 𝑠𝑖𝑛2 𝑥 = 2 cos 2𝑥
𝑧 𝑧̅
| + | = |2 cos 2𝑥| = 2| cos 2𝑥 |
𝑧̅ 𝑧
Hence possible values of 𝑧 are:
𝑧 = cos 𝑥 + 𝑖 sin 𝑥, where
𝜋 𝜋 2𝜋 5𝜋 7𝜋 4𝜋 5𝜋 11𝜋
𝑥= , , , , , , ,
6 3 3 6 6 3 3 6
3. (a) Assume that the inverse of 𝐴 is not unique. Hence let 𝐵 and 𝐶 both be
inverses of 𝐴. Then we have
𝐴𝐵 = 𝐵𝐴 = 𝐼𝑛 and 𝐴𝐶 = 𝐶𝐴 = 𝐼𝑛
𝐵 = 𝐵𝐼𝑛 = 𝐵(𝐴𝐶) = (𝐵𝐴)𝐶 = 𝐼𝑛 (𝐶) = 𝐶
Since 𝐵 = 𝐶, if 𝐴 is invertible then its inverse is unique.

(b) 𝐴𝐵 = 𝐵𝐴
𝑎 𝑏 𝑑 𝑒 𝑑 𝑒 𝑎 𝑏
↔[ ][ ]=[ ][ ]
0 𝑐 0 𝑓 0 𝑓 0 𝑐
𝑎𝑑 𝑎𝑒 + 𝑏𝑓 𝑎𝑑 𝑐𝑒 + 𝑏𝑑
↔[ ]=[ ]
0 𝑐𝑓 0 𝑐𝑓
↔ 𝑏𝑑 + 𝑐𝑒 = 𝑎𝑒 + 𝑏𝑓
↔ 𝑏𝑑 − 𝑏𝑓 − (𝑎𝑒 − 𝑐𝑒) = 0
↔ 𝑏(𝑑 − 𝑓) − 𝑒(𝑎 − 𝑐) = 0
𝑏 𝑎−𝑐
↔| |=0
𝑒 𝑑−𝑓
𝑏 𝑎−𝑐
Hence 𝐴𝐵 = 𝐵𝐴 if and only if | | = 0.
𝑒 𝑑−𝑓

(c)
(i) There exist constants 𝑐1 , 𝑐2 , 𝑐3 , … , 𝑐𝑛 ∈ ℝ such that 𝑣 can be expressed as
𝑐1 𝑣1 + 𝑐2 𝑣2 + 𝑐3 𝑣3 + ⋯ + 𝑐𝑛 𝑣𝑛

(ii) The only solution to the system of equations


c1v1  c2 v2  c3 v3  ...  cn vn  0
~
is 𝑐1 = 𝑐2 = 𝑐3 = ⋯ = 𝑐𝑛 = 0.

There exists a solution to the system of equations


(iii)
c1v1  c2 v2  c3 v3  ...  cn vn  0
~

Such that at least one of 𝑐1 , 𝑐2 , 𝑐3 , … , 𝑐𝑛 ≠ 0.

(d) (−1, −4,5) = 𝑐1 (1,4, −1) + 𝑐2 (0,3, −4) + 𝑐3 (−1,2, −3)


= (𝑐1 − 𝑐3 , 4𝑐1 + 3𝑐2 + 2𝑐3 , −𝑐1 − 4𝑐2 − 3𝑐3 )
Equating each component,
𝑐1 − 𝑐3 = −1 − (1)
4𝑐1 + 3𝑐2 + 2𝑐3 = −4 − (2)
−𝑐1 − 4𝑐2 − 3𝑐3 = 5 − (3)
(2) − 4(1): 3𝑐2 + 6𝑐3 = 0 − (4)
(1) + (3): −4𝑐2 − 4𝑐3 = −4 − (5)
Solving (4) and (5) yields 𝑐2 = −2, 𝑐3 = 1,
hence 𝑐1 = 𝑐3 − 1 = 0.
Therefore
(−1, −4,5) = 0(1,4, −1) − 2(0,3, −4) + (−1,2, −3).

4. (a) −9 4 4
(i) 𝐴 = [ −8 3 4]
−16 8 7
−9 − 𝜆 4 4
|𝐴 − 𝜆𝐼3 | = | −8 3−𝜆 4 |
−16 8 7−𝜆
Performing elementary row operations;
−9 − 𝜆 4 4 −2𝑅2 +𝑅3 →𝑅3 −9 − 𝜆 4 4
| −8 3−𝜆 4 | = → | −8 3 − 𝜆 4 |
−16 8 7−𝜆 0 2 + 2𝜆 −1 − 𝜆
−9 − 𝜆 4 4
= (1 + 𝜆) | −8 3−𝜆 4 |
0 2 −1
Expanding along the third row,
−9 − 𝜆
4 −9 − 𝜆 4
−(1 + 𝜆) [2 | |+| |]
−8 4 −8 3−𝜆
= −(1 + 𝜆)[2(32 − 36 − 4𝜆) + (9 + 𝜆)(𝜆 − 3) + 32]
= −(1 + 𝜆)(−8 − 8𝜆 + 5 + 𝜆2 + 6𝜆)
= −(1 + 𝜆)(𝜆2 − 2𝜆 − 3)
Characteristic polynomial, 𝑝(𝜆) = −𝜆3 − 𝜆2 + 5𝜆 + 3

(ii)
When 𝑝(𝜆) = 0, (1 + 𝜆)(𝜆2 − 2𝜆 − 3) = 0
(1 + 𝜆)(𝜆 + 1)(𝜆 − 3) = 0
Hence matrix A has eigenvalues -1, -1 and 3.
When 𝜆 = −1:
−9 + 1 4 4 𝑥 0
| −8 3+1 𝑦
4 | [ ] = [0]
−16 8 7+1 𝑧 0
−8𝑥 + 4𝑦 + 4𝑧 = 0, − 8𝑥 + 4𝑦 + 4𝑧 = 0, − 16𝑥 + 8𝑦 + 8𝑧 = 0
The solution is 𝑥 = 𝑠, 𝑦 = 𝑡, 𝑧 = 2𝑠 − 𝑡, 𝑠, 𝑡 ∈ ℝ.
𝑥 1 0 1 0
[𝑦] = 𝑠 [0] + 𝑡 [ 1 ], corresponding eigenvectors are [0] and [ 1 ].
𝑧 2 −1 2 −1
When 𝜆 = 3:
−9 − 3 4 4 𝑥 0
| −8 3−3 4 | [𝑦] = [0]
−16 8 7−3 𝑧 0
−12𝑥 + 4𝑦 + 4𝑧 = 0, −8𝑥 + 4𝑧 = 0, −16𝑥 + 8𝑦 + 4𝑧 = 0
The solution is 𝑥 = 𝑡, 𝑦 = 𝑡, 𝑧 = 2𝑡, 𝑡 ∈ ℝ.
𝑥 1 1
[𝑦] = 𝑡 [1], corresponding eigenvector is [1].
𝑧 2 2

Hence the matrix has eigenvalues -1, -1 and 3 with corresponding


1 0 1
eigenvectors[0], [ 1 ], [1].
2 −1 2

1 0 1 −1 0 0
(iii) 𝑃 = [0 1 1 ] , 𝐷 = [ 0 −1 0]
2 −1 2 0 0 3

(b) 𝑝(𝜆) = 0, 𝜆3 + 𝜆2 − 5𝜆 − 3 = 0
Applying Cayley-Hamilton’s theorem:
𝐴3 + 𝐴2 − 5𝐴 − 3𝐼3 = 03
𝐴3 𝐴−1 + 𝐴2 𝐴−1 − 5𝐴𝐴−1 − 3𝐼3 𝐴−1 = 03 𝐴−1
𝐴2 + 𝐴 − 5𝐼3 − 3𝐴−1 = 03
3𝐴−1 = 𝐴2 + 𝐴 − 5𝐼3
1 1 5
𝐴−1 = 𝐴2 + 𝐴 − 𝐼3
3 3 3